# Where did I go wrong in expanding the brackets?

• Oct 22nd 2012, 10:02 AM
Ashir
Where did I go wrong in expanding the brackets?
11-3(x+2) =
8(x+2) =
8x+16

• Oct 22nd 2012, 10:18 AM
skeeter
Re: Where did I go wrong in expanding the brackets?
Quote:

Originally Posted by Ashir
11-3(x+2) =
8(x+2) =
8x+16

you did not follow the order of operations ...

11 - 3(x+2) =

11 - 3x - 6 =

5 - 3x
• Oct 22nd 2012, 10:18 AM
bjhopper
Re: Where did I go wrong in expanding the brackets?
Quote:

Originally Posted by Ashir
11-3(x+2) =
8(x+2) =
8x+16

remove brackets first to get -3x - 6 then do the addition-subtraction
• Oct 22nd 2012, 10:22 AM
Ashir
Re: Where did I go wrong in expanding the brackets?
Oh, thanks. But why couldn't I subtract 3 from 11 first?
• Oct 22nd 2012, 10:42 AM
skeeter
Re: Where did I go wrong in expanding the brackets?
Quote:

Originally Posted by Ashir
Oh, thanks. But why couldn't I subtract 3 from 11 first?

The Order of Operations: PEMDAS
• Oct 23rd 2012, 09:29 AM
Ashir
Re: Where did I go wrong in expanding the brackets?
I got it, thanks for the help!